Perbedaan Model Pembelajaran Problem Solving dan Problem Based Learning Berbantuan Papan Diagram terhadap Kemampuan Pemecahan Masalah Siswa Sekolah Dasar - Yunita Berliana Nurul Hidayah; Lisa Virdinarti Putra (Journal on Education, 2023)
This study aims to determine the significant differences between the Problem Solving learning model based on Blended Learning and PBL based on Blended Learning assisted by Board Diagrams on the problem solving abilities of grade 5 students. This research method is a quantitative experimental research. The population in this study were all fifth grade students at SD Negeri Batursari 6. The research sample was VA class as the experimental group I totaling 26 students with the Problem Solving model and VC class as the experimental group II totaling 28 students with the PBL (Problem Based Learning) model. The results showed that there were differences in the use of the PBL Model based on Blended Learning assisted by Board Diagrams on the problem solving abilities of grade 5 students. The results of the independent sample t- test showed a significance level of <0.05, namely 0.004 <0.05, then Ha was accepted.